Pengaruh Penerapan Sistem Manajemen Sumber Daya Perusahaan (ERP) dalam Meningkatkan Kinerja Manajemen Rantai Pasok (SCM) Kafe Catarina - Immanuel Zai; Stefhani Susanto; Fionna Angeline; Keltine Richelle Chan; Katherine Katherine; Michelle Go; Putry Surya (STIE AMKOP, 2023)
In an era where all of these technological improvements have become commonplace, business movements are becoming very competitive. To maintain its competitiveness, a business must implement a competent and appropriate enterprise resource management (ERP) system that affects the performance of the business's Supply Chain Management (SCM). Catarina Cafe is a food and beverage business that has been operating since 1996. Catarina Cafe was chosen as the research subject in this project because of the consistency of product quality, high food taste, and comfortable cafe interior design, as well as its strategic location because it is in the middle of city, easy to find, has a large parking lot, and is frequently visited, so it has high opportunities for future business development. In this study, the authors will examine the performance of supply chain management (SCM) which is affected by the application of Catarina Cafe's enterprise resource management system (ERP) from the point of view of the sales process. This research was conducted using a qualitative descriptive research method and data collection was carried out through observation and interviews. Based on the research conducted, it can be concluded that Catarina Cafe has adopted effective enterprise resource management (ERP) sales procedures that result in customer satisfaction for Catarina Cafe's business. The limitations that the authors have in this study, namely the lack of quantitative data that can be analyzed so that the research cannot be carried out optimally. This research is expected to produce a solution to achieve the expected goals and stages of activities that can develop the Catarina Cafe business, especially in supply chain management (SCM) performance activities. This report discusses the supply chain management (SCM) performance activities of Catarina Cafe which are identified in the literature with the sales process theory or sales process under the influence of enterprise resource management (ERP) implementation. Keywords: Catarina Cafe, ERP, SCM, Sales Process